INTEGRATING THE ROLE OF THE TEACHER IN TECHNOLOGICAL DEVELOPMENT: BUILDING A BRIDGE BETWEEN TRADITIONAL AND DIGITAL LEARNING - Didik Cahyono; Mukni'ah; Moh. Imron Rosidi; Eliagus Telaumbanua; Agus Rofi'i (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Technology in education is a system used to support learning to produce desired targets. Indonesian technology implementation states that technology can be used as a learning intermediary, management tool and learning resource. The development of science and technology has had a positive influence on increasing openness and the spread of knowledge across space and time on a global scale. The teacher is the only source of learning for students. In this educational interaction pattern, the class teacher dominates teaching and learning activities. This teaching pattern does not or does not provide opportunities for the use of technology in teaching. Books, blackboards, teaching media, libraries have not played a role in the teaching and learning process. Such teaching patterns do not provide space for the development of technology in teaching. In facing improvements in the quality of education in the digital era, the role of teachers is very much needed. However, in practice, teachers face several challenges in the world of education in the digital era, such as: developments in technology and information have an impact on the increasingly rapid development of science.